2013
DOI: 10.4103/2249-4863.117404
|View full text |Cite
|
Sign up to set email alerts
|

Structured printed referral letter (form letter); saves time and improves communication

Abstract: Referral of patients to hospitals, specialists and other institutions is an essential part of primary health care. Patients are referred to specialists when investigation or therapeutic options are exhausted in primary care or when opinion or advice is needed from them. Referral has considerable implications for patients, health care system and health care costs. Good communication between primary and secondary care is essential for the smooth running of any health care system. Referral and reply letters are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…At present, little face-to-face communication is conducted among health service providers. Written correspondence is the most common tool for information transfer involving patient care 3 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, little face-to-face communication is conducted among health service providers. Written correspondence is the most common tool for information transfer involving patient care 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the implementation of structured documentation, systems and training is urgently required to manage critical care transitions such as referrals, transfers and discharge. Research from both HIC and LMIC settings has proven that such interventions can improve the continuity and safety of care 4 17 37 49. Regarding future steps, during HCP interviews it was reported that public healthcare facilities in Kerala will be transitioning to computerised ‘e-health’ information systems.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, the use of standardized referral forms can help increase the amount of valuable information transmitted in this manner. 38 , 39 The Cambodia MOH had created and recommended the use of a standardized referral slip during all patient referrals 40 , however the form they created lacked adequate structure to promote quality information transfer, particularly around the details of care provided to maternity patients, pediatric patients, and neonatal patients. To increase the impact of this referral-communication tool, the project updated the referral slip to improve its ability to efficiently capture practice-changing information.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%